Food Additive Safety Education to Enhance Awareness among Students of Al-Azhar 11 Islamic Elementary School, Surabaya - Muslikh, Faisal Akhmal (TRI DHARMA MANDIRI: Dissemination and Downstreaming of Research to the Community (Journal of Community Engagement), 2025)
The habit of consuming snacks among elementary school students can pose serious health risks due to the use of hazardous food additives such as borax, formalin, saccharin, and Rhodamine B. The lack of students’ understanding regarding the dangers of these substances prompted the implementation of an educational program at Al-Azhar 11 Islamic Elementary School in Surabaya on October 26, 2024. The educational session was delivered through a lecture combined with comic-based media and attended by 110 students from grades 3 to 6. To evaluate the program’s effectiveness, students were given pre-tests and post-tests. The analysis showed an increase in students’ understanding from 39.72% to 60.27%, indicating that the applied educational method was effective. Despite the limited duration, students’ enthusiasm and the school’s support contributed to the smooth execution of the activity. This initiative highlights the importance of early education in food safety as a preventive measure to promote healthier eating habits and reduce the risk of foodborne illnesses associated with unsafe snacks in school environments.